2023
DOI: 10.1021/acs.est.2c09554
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of Urinary Mercapturic Acids Using Integrated Library-Guided Analysis

Abstract: Urinary mercapturic acids (MAs) are often used as biomarkers for monitoring human exposures to occupational and environmental xenobiotics. In this study, we developed an integrated library-guided analysis workflow using ultraperformance liquid chromatography–quadrupole time-of-flight mass spectrometry. This method includes expanded assignment criteria and a curated library of 220 MAs and addresses the shortcomings of previous untargeted approaches. We employed this workflow to profile MAs in the urine of 70 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Ayala et al quantitatively measured the urinary excretion of naphthalene metabolites and found that GSH and MA accounted for >60% of the total measured metabolites in mice. MA s have also been identified as urinary metabolites in humans . Contrary to the findings of Ayala et al, MA s have been characterized as minor metabolites in cigarette smokers .…”
Section: Resultsmentioning
confidence: 63%
“…Ayala et al quantitatively measured the urinary excretion of naphthalene metabolites and found that GSH and MA accounted for >60% of the total measured metabolites in mice. MA s have also been identified as urinary metabolites in humans . Contrary to the findings of Ayala et al, MA s have been characterized as minor metabolites in cigarette smokers .…”
Section: Resultsmentioning
confidence: 63%
“…Structure-oriented monitoring methods are employed for the detection of multiple classes of toxicologically or pharmacologically relevant compounds. In contrast to unbiased-shotgun methodologies, structure-oriented monitoring utilizes prior knowledge of the elemental composition, structural moiety, or functional group characteristics to develop an analytical pipeline honed for the detection of a subset of compounds. , Fragmentation-based LC–MS/MS methods are routinely used to characterize phase I and phase II metabolites such as cysteinyl, , sulfate, ,, or glucuronide conjugated products. ,, Additionally, discovery methods have been developed to monitor for specific classes of clinically relevant molecules by diagnostic fragmentation patterns, including steroid hormones, covalently modified DNA and RNA nucleosides, , and small molecules or peptides exhibiting glycosylated, phosphorylated, or other distinct functional groups modifications. Early stage drug discovery requires extensive characterization of drug metabolism, including description of drug-related metabolites, potential reactive intermediaries, and degradation products. ,, To characterize this array of metabolically diverse drug intermediates, structure-oriented monitoring approaches were developed to screen predictable transformations frequently occurring in vivo , such as hydroxylation, dehydrogenation, and demethylation, among other common phase I or II conjugation reactions. , These approaches have been used to discover numerous drug biproducts and nerve agents and their degradation products. , …”
Section: Introductionmentioning
confidence: 99%